PENINGKATAN PRODUKTIFITAS PENGUSAHA MIKRO TAHU SUKUN MALANG - Maria, Evi; Kadarusman, Kadarusman; Irawati, Rina (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2019)
Abstract: In addition to being known as the city of Malang chips tempe and fruit chips, also known as tofu which is commonly referred to by the community as "Breadfruit Tofu". Sukun is the name of one of the sub-districts in Malang, which consists of several villages including Sukun and Tanjungrejo. In the Sukun village there is a tofu industry that is quite large, namely "Tahu 73". Tofu is what is known by the people of Malang as "Tahu Sukun". In Tanjungrejo village, which is located next to Sukun village, there are several tofu entrepreneurs who are still on a micro scale or still in the form of a home industry. Tofu entrepreneurs in Tanjungrejo village are hereditary activities and are a source of income. The establishment of this tofu business aims to meet the daily needs of partners and in the future to create broader employment opportunities for the surrounding community. The problems faced by Mitra Uasha are that the milling tools and machinery are not feasible, many are porous, filtering tools are very simple, production sites are not clean, plastic tubs for tofu and for sale are already many that are not feasible, as well as for the kegs and knowledge very limited regarding bookkeeping and management of its business management because its human resources are still very low. To achieve these goals and targets in the implementation of the PKM program carried out with a family approach so that there is strong cooperation with partners, training and assistance in making simple bookkeeping, marketing and entrepreneurship, training in product innovation based on tofu and monitoring Keyward: microbusiness, tofu